ENHANCING ENTREPRENEURIAL INTEREST THROUGH BUSINESS MODEL CANVAS TRAINING FOR PRIVATE HIGH SCHOOL STUDENTS IN SURABAYA - Tanuwijaya, Haryanto; Supriyanto, Antok (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aimed to increase entrepreneurial interest among private high school students in Surabaya through Business Model Canvas (BMC) training. The program was motivated by the limited practical entrepreneurship learning in schools, which caused students to have low understanding and interest in entrepreneurship. The activity was conducted at two private high schools in Surabaya involving 240 students. The implementation method consisted of preparation, training, practice, mentoring, and evaluation stages. The training materials included entrepreneurship concepts, business opportunities in the digital era, and the preparation of business models using the Business Model Canvas approach. Evaluation was carried out using pre-test and post-test methods, questionnaires, and participatory observation. The results showed an increase in students’ understanding of entrepreneurship by 21.67%, understanding of Business Model Canvas by 34.17%, and entrepreneurial interest by 47.91%. The average evaluation score of the training implementation reached 4.52 on a Likert scale of 5, indicating that the activity was well implemented and positively received by participants. The training also encouraged students’ creativity, critical thinking, collaboration, and confidence in presenting business ideas. Therefore, Business Model Canvas training can be an effective practical entrepreneurship learning method to support entrepreneurial competency development among high school students